Factors associated with choosing psychiatry among medical interns in two private universities in Peru - Cedillo Ramírez, Lucy Perla Gulliana (2019)
Objective: To determine the factors associated with choosing psychiatry as a specialty among medical interns in two private universities in Peru. Methods: A cross-sectional study was carried-out among medical interns of Ricardo Palma and San Juan Bautista Universities. Three instruments were applied: personality inventory-Eysenck for adults, scale to evaluate the teaching-learning process and the Goldberg´s general survey of mental health to evaluate personality, perception of the teaching-learning process of the psychiatry and psychology courses. The X2 test was used to determine associations. Results: out of 233 medical interns evaluated, 35 (15.7%) said that would elect psychiatry as a specialty. The election of psychiatry was associated with a blood personality (p=0.001); extroversion (p=0.02) and being emotionally stable (p=0.039). On the other hand, the study did not reveal and association with sex, relatives with specialties closed to mental health and psychopathology. Conclusions: there is an association between type of personality and choosing psychiatry as a) specialty. Medical interns interested in becoming psychiatrist have a blood type of personality, are extroverted and emotionally stable.